The Influence of Macro Variables on Economic Growth in Indonesia - Samin Saputra; Cicih Ratnasari; Dedi Suwardi Bahagia (MultiTech Publisher, 2025)
Economic growth is an important indicator in assessing the progress of a country, including Indonesia. Various macroeconomic factors can affect this growth, and a deep understanding of the relationship between these variables is essential to formulating effective policies. This study aims to analyze the influence of macroeconomic variables, namely inflation, Human Development Index (HDI), labor wages, digital technology transformation, and manufacturing industry on economic growth in Indonesia. This study uses a quantitative approach with panel data regression analysis to test the relationship between independent and dependent variables. The data used includes secondary data from various official sources such as the Central Statistics Agency (BPS) from 2013 to 2023 in 12 provinces in Indonesia. The results of the analysis show that inflation has a negative impact on economic growth, while HDI, labor wages, and digital technology transformation show a significant positive effect. In addition, the manufacturing industry also contributes positively to economic growth. This finding emphasizes the importance of price stability and improving the quality of human resources and adopting technology in driving economic growth. The conclusion of the research results is that macroeconomic variables have an important role in influencing economic growth in Indonesia. Therefore, policies that focus on controlling inflation, increasing HDI, adjusting labor wages in accordance with productivity, and supporting digital transformation and the manufacturing sector need to be prioritized to achieve sustainable economic growth.